The complete guide to medications during pregnancy and breast-feeding : everything you need to know to make the best choices for you and your baby - Weiner, Carl P. (St. Martin's Griffin, 2013)
"Even the average OB-GYN is confused about what drugs are safe for pregnant and breastfeeding women to take. Tylenol, Ambien, Sudafed? How much is ok? When? Misinformation, an out-dated FDA classification system, and fear all stand in the way. The result: OB's often fail to prescribe needed medications or prescribe the wrong medications to their patients. Written specifically for lay-readers by a maternal-fetal medicine expert and a veteran health reporter, The Complete Guide to Medications During Pregnancy and Breastfeeding takes the confusion out of the process, combining authority, advice, an A-to-Z directory of more than six hundred drugs, and empathy. With easy to understand entries covering hundreds of drugs, this volume will help mothers make informed choices for themselves and their babies"--